Evaluating lean thinking using value stream mapping in manufacturing industry - a case study. (2017) - Singh, Jagdeep; Singh, Harwinder; Singh, Deepinder; Singh, Kultaran
Value stream mapping is an important lean manufacturing tool used to improve business in a competitive market by eliminating non-value adding activities or wastes from the value stream of a product and improving in providing in process operations. This paper aims to address the application of lean manufacturing using value stream mapping (VSM) concepts in a casting organisation. Using value stream concepts, both current and future states maps of the organisation's shop floor scenarios have been discussed. Results of investigation demonstrated the net reduction of 14.28% in value added time and net cycle time of operation is reduced from 12 minutes to 9 minutes. Current state map and future state map are compared and important benefits occurred after successful implementation of VSM has been discussed and it leads to profit of about 357000 rupees annually.